Platemaking composite fiber cement advantage industrial waste rice hulls and sludge from the manufacturing process of white paper as a building material inexpensive - Camus Loredo, Jorge (2014)
In Peru generated 140,000 and 13,000 MT / year of rice husks and scrap of paper industry respectively, without commercial value and not industrial use. 8.51%, ash: 20.71%, ether extract 0.73%, protein 1.59%, crude fiber 39.75 ashes of the paper used (63.47 ± 0.805% db) and a chemical-proximal of the scale (moisture analysis were determined % and carbohydrates: 28.71% db). Scale (5- 15%), cement (30-50%), gypsum (15-25%), rubber (10%) and paper sludge (10-20%) formulations were designed. Plates were characterized by: Brinell test (hardness, brittleness and compaction), density, heat capacity, shear strength, screw pump test, resistance to freeze / thaw and combustibility test. 8 of the 31 formulations tested had excellent physical properties and can be used in building construction. The research demonstrates the feasibility of manufacturing fiber cement board good quality, satisfactory to the construction industry at low cost.